2013
DOI: 10.1179/2046905512y.0000000036
|View full text |Cite
|
Sign up to set email alerts
|

Timing of umbilical cord-clamping and infant anaemia: the role of maternal anaemia

Abstract: The study contributes additional evidence in support of delayed cord-clamping. This intervention is likely to have most public health impact in areas with a high prevalence of anaemia during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…A questionnaire, which included questions on socio-demographic and health information about the child and family, was then administered by the RA during a household interview with that parent who was the primary caregiver. The questionnaire was adapted from previous studies [8] , [21] [23] , but included additional questions related to child nutrition. These included history and duration of breastfeeding, and first introduction of liquids and solid foods.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire, which included questions on socio-demographic and health information about the child and family, was then administered by the RA during a household interview with that parent who was the primary caregiver. The questionnaire was adapted from previous studies [8] , [21] [23] , but included additional questions related to child nutrition. These included history and duration of breastfeeding, and first introduction of liquids and solid foods.…”
Section: Methodsmentioning
confidence: 99%
“…At face value, the results support the efficacy of the project in promoting DCC, but changing practice from waiting to the cord stops pulsating to clamping at 3 min deserves some reflective assessment about the project design including implications for future practice change interventions and cultural influences on behaviours. Having a policy and procedure in place has been reported as significantly supporting adoption of new practice (Blouin et al 2013) and having institutional support promotes the effectiveness of maternal and child health services (Rao 2012). It is possible that the NICE Foundation policy and procedure influenced the uptake of DCC as much as the workshop although we do not have evidence to support this statement.…”
Section: Discussionmentioning
confidence: 80%
“…6,10,11 One of the more widely accepted of these consequences is the increase in placenta-to-infant blood volume transfer, supplying an additional 30 to 75 mg of iron at delivery. 12 The concerns about delayed cord clamping include the possibility of polycythemia, hyperviscosity, hyperbilirubinemia, transient tachypnea of the newborn, delay in resuscitation, hypothermia, and a possible risk of intraventricular hemorrhage. 11 On the other hand, several studies have reported that parturition features a strong oxidative stress for both mother and neonate, implying an increased production of free radicals that must be controlled by their antioxidant systems.…”
mentioning
confidence: 99%